Effect of low-dose volatile anesthetics on intraoperative neurophysiological monitoring during anesthesia with remimazolam - Hee-Sun Park; Wonho Choi; Dong-Ho Lee; Yong Seo Koo; Se Keun Oh; Won Uk Koh (Korean Journal of Anesthesiology)
Background Remimazolam is a novel short-acting benzodiazepine. We investigated the effects of low doses of volatile anesthetic agents on motor evoked potentials (MEPs) and somatosensory evoked potentials (SSEPs) during remimazolam-remifentanil anesthesia. Methods Thirty-nine patients undergoing cervical spine surgery were randomly assigned to either the sevoflurane (n = 20) or desflurane (n = 19) groups. Volatile anesthetic agents were administered at 0.3, 0.6, and 0.8 minimum alveolar concentrations (MACs) during remimazolam-remifentanil anesthesia. Significant changes were considered as more than 50% amplitude suppression and more than 10% latency increase from baseline values. The primary outcome was MEP amplitude change. Secondary outcomes included MEP latency, SSEP amplitude and latency, and group comparisons. Results The MEP amplitudes were slightly reduced at 0.3 MAC; however, a suppression of more than 50% from baseline values at 0.3 MAC, particularly in the upper limbs, was observed in a notable proportion of participants; 30.0% and 47.4% in the sevoflurane and desflurane groups, respectively. The corresponding percentages for the lower limbs were 15.0% and 15.8%, respectively. MEP amplitude suppression was more than 50% in the majority of participants at 0.6 and 0.8 MAC. No significant difference was observed between the groups. SSEPs exhibited no significant amplitude suppression or latency prolongation across all MAC levels. Conclusions Notable MEP amplitude suppression was observed in many patients when 0.3 MAC volatile anesthetics were used as adjuncts. Therefore, even low doses of volatile anesthetics must be added cautiously to remimazolam-based anesthesia to prevent confounding. The SSEPs were relatively preserved, regardless of MAC.